Criminal Law Arrangements in Handling the Spread of Social Media Bot-Based False Information in Indonesia - Judijanto, Loso; Putra, Irman; Sumarni, Sumarni (The Easta Journal Law and Human Rights, 2025)
This study examines the legal arrangements in Indonesia for handling the spread of false information through social media bots, employing a normative juridical analysis. The proliferation of disinformation through automated bots has become a significant challenge to public trust, social cohesion, and democratic processes. This paper explores the adequacy of existing legal frameworks, such as the Information and Electronic Transactions Law (ITE Law), the Indonesian Penal Code, and the Election Law, in addressing bot-generated false information. The study identifies key challenges, including technological limitations, legal ambiguities, and jurisdictional issues, and compares Indonesia’s regulatory approach with that of the European Union and the United States. The research highlights the need for clear legal definitions, enhanced platform accountability, improved enforcement capabilities, and greater international cooperation to effectively address this issue. The study concludes with recommendations for legal reforms and increased public awareness to mitigate the adverse impact of social media bots on public discourse in Indonesia.